Clinical method, ‘’good clinical practices’’, and medical professionalism - Miguel Ángel Moreno Rodríguez (Medisur)
Medicine, in its widest conception, is the science and art to know, prevent, relieve, and cure illnesses. It is pointed out that the clinical method is the scientific or experimental method of science applied to the attention of an individual patient, but in this case the experimental stage is replaced by the confrontation with diagnostic technology. Therapy is also currently included into the clinical method by many authors. It is emphasized that this method should be the first and most valuable of all “good clinical practices”. Some principles for an adequate application of the clinical method are: a good doctor-patient relationship, the individualization of each patient, the great value of clinics (especially the interview and the physical examination) and the role of technology in the process of diagnosis. It is should be highlighted that medical clinics and its method are more important today than in the past. It is therefore necessary that teachers educate their students, both in theory and practice, in an exquisite use of the clinical method.